To the memory of Joseph Gottfrid Thulin (Fiep Bulletin - online, 2015)
The A. praises the great work undertaken by the former President of the “F.I.E.P.” in Lund, and Sums up the general ideas that would have had inspired Him: Thulin adopted ling,s fundamental principle: “Bodily exercises should be subordinated to the laws which rule the human being.”